Arachidonate 15-lipoxygenase-mediated production of Resolvin D5n-3 DPA abrogates pancreatic stellate cell-induced cancer cell invasion - Aguirre, Gabriel A.; Goulart, Michelle R.; , Barts Pancreas Tissue Bank; Dalli, Jesmond; Kocher, Hemant M. (Frontiers in Immunology, 2023)
Activation of pancreatic stellate cells (PSC) to cancer-associated fibroblasts (CAF) is responsible for the extensive desmoplastic reaction observed in PDAC stroma: a key driver of pancreatic ductal adenocarcinoma (PDAC) chemoresistance leading to poor prognosis. Specialized pro-resolving mediators (SPMs) are prime modulators of inflammation and its resolution: traditionally thought to be produced by immune cells. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based lipid mediator profiling PSCs as well as primary human CAFs express enzymes and receptors to produce and respond to SPMs. Human PSC/CAF SPM secretion profile can be modulated by rendering these cells activated (transforming growth factor beta (TGF-β)) or quiescent (all-trans-retinoic-acid (ATRA)). ATRA-induced nuclear translocation of arachidonate-15-lipoxygenase (ALOX15) was linked with increased production of n-3 docosapentaenoic acid-derived Resolvin D5 (RvD5 n-3 DPA), amongst other SPMs. Inhibition of RvD5n-3 DPA formation increases cancer cell invasion, whereas addback of this molecule reduced activated PSC mediated cancer cell invasion. We also observed that circulating concentrations of RvD5n-3 DPA levels were decreased in peripheral blood of metastatic PDAC patients when compared with those measured in plasma of non-metastatic PDAC patients. Together these findings indicate that RvD5n-3 DPA may regulate cancer-stroma crosstalk and invasion.